Diversification in banking and its effect on banks’ performance: evidence from Turkey - Yılmaz Türkmen, Sibel; Yiğit, İhsan (My University, 2012)
This paper examines the effect of sectoral and geographical diversification on the performance of Turkish banks and try to show how the diversification affects banks’ performance. The study asks whether diversification via sectoral and geographical credits helps banks. To investigate the relationship between the credit diversification and performance of 50 Turkish banks between the time period of 2007 and 2011, data sources of Banking Regulation and Supervision Agency (BRSA), The Banks Association of Turkey (BAT) and Istanbul Stock Exchange (ISE) is used. Because of the mergers and acquisitions and being closed, it is failed to reach some of bank data in 2007-2011. In this manner the study is analysed on 40 banks’ data. In the present study, ROA (Return on Assets) and ROE (Return on Equity) are used as measure of performance and Herfindahl Index (HI) is used as a measure of diversification of banks. The number of credits and the amount of credits that banks let borrewers’ use are employed as control variables. According to the result of the analysis it is determined that dependent variables ROA and ROE are explained by diversification.
Keywords: Credit diversification; Herfindahl index; Bank performance; ROA; ROE